THE STUDENTS’ LEARNING STYLES IN DEBATE CLASS AT ENGLISH DEPARTMENT OF ISLAMIC UNIVERSITY KALIMANTAN MUHAMMAD ARSYAD AL BANJARI - Muhammad Fajeri; Raudhatul Haura; Angga Taufan Dayu (Intensive Journal, 2018)
Mapping the students’ learning style can make easier the educators to choose the suitable teaching strategies. This research investigated the students’ learning styles in debate class in order to find out what is the most dominant learning style and what is the least interested learning style.The researcher used a quantitative method and intangible sample survey technique in cross sectional time to gain the result. The researcher used learning style questionnaire as the instrument to collect the data and learning style instrument to analize the data. This research was using Proportionate random sampling technique (60%), there were 71 students took as sample of research from third semester of Islamic University Kalimantan Muhammad Arsyad Al Banjari.As the result found out that the most dominant learning style in debate class was kinesthetic with 39% or 28 students choosed it as their best style in learning and the least interested learning style in debate class was visual learning style with 29% or 20 students did not like study using visual aid. Based on the result above, the educators should create learning environment more active, enhancing their physical interaction and avoid the strategy using any visual aid.